Protection of Civil Rights in a Federal State of Ethiopia during the State of Emergency Declared due to COVID-19 - Liyew, Estifanos Balew; Moges, Seifu (Ethiopian Journal of Social Sciences, 2021)
The study assesses the enforcement and protection of civil rights in the enforcement process of the state of emergency law enacted to counter and control the spread of COVID-19 in the Afar Region, Ethiopia. To investigate the problem, the research employs a qualitative approach with a non-probability sampling techniques. In addition to the primary data collected through fielded interview and focus group discussion, secondary data was collected from journal articles, books, proclamations, human rights instruments, and reports. The findings of this research revealed that in the state of emergency declared to control the COVID-19 outbreak, civil rights infringement was observed due to lack of awareness, negligence, and resistance to observing the state of emergency law on the part of the people and due to systemic pitfalls, shortage of skilled manpower and commitment by the law enforcement agencies in their attempt to implement the state of emergency law.